Reply to "comment on 'new experimental data and reference models for the viscosity and density of squalane" - Schmidt,KAG; Pagnutti,D; Trusler,JPM (Journal of Chemical and Engineering Data, 2015)
The authors would like to thank Professor Bair for his insightful comments on ultrahigh-pressure viscosities. The viscosity model used by Schmidt et al.1 was a Tait-like2,3 model that has been shown to correlate accurately the viscosity of many fluids in the original investigation’s pressure range (0.1–275.8 MPa (40000 psi)) of interest. The upper pressure is indicative of the high pressures found in the petroleum industry4. However, after discussions with Professor Bair, it became clear a reference model that can accurately model the viscosity of squalane at ultrahigh-pressures is of interest to those working in the area of tribology.